Media, Health & Health Promotion in Nepal - van Teijlingen, Edwin; Simkhada, Padam; Luce, Ann; Hundley, Vanora (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
It has been recognised that the media can affect our perceptions, views and tastes on a wide-range of issues. The mass media in it various forms (newspapers, television & radio, the internet and Twitter) and formats, have a far reaching influence through, for example news programmes, documentaries, advertising and entertainment. At the same time the media can also be seen as a channel for agencies responsible for public health to get their messages across to the population. Public health agencies are always searching for ways to disseminate health information and messages to their intended audiences. These are, of course, global concerns, but as both public health and the media are part of the society in which they operate there will be locally specific issues and considerations. To date most of the research into the media and public health has been conducted in high-income countries, and there has been very little research in Nepal on the interaction of public health and health promotion with the media. This overview paper highlights some of the key issues that public health practitioners, media editors and journalists, health policy-makers and researchers could consider. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.70-75